2011
DOI: 10.1007/s11670-011-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study to determine MTD of docetaxel and cisplatin with concurrent radiation therapy for stage III non-small cell lung cancer

Abstract: Objective: To evaluate the maximum tolerated dose (MTD) of docetaxel (DCT) and cisplatin (DDP) concurrently with three dimensional (3D) conformal radiotherapy or IMRT for patients with locally advanced non-small cell lung cancer (stage IIIa and IIIb) after 2-4 cycles of induction chemotherapy.Methods: Fourteen patients with histological/cytological proven stage III non-small-cell lung cancer were eligible. 3D or IMRT radiotherapy (60-70Gy in 30-35 fractions, 6-7weeks, 2 Gy/fraction) was delivered concurrently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To date, DTX has been shown to be clinically useful as an active agent in CRT treatment regimens involving laryngeal/hypopharyngeal cancers (19). DTX has been used in combination with cisplatin as an agent for CRT in non-small cell lung cancer (20). A phase I/II study involving DTX and cisplatin with concurrent thoracic radiotherapy for locally advanced non-small cell lung cancer has shown that the dose limiting toxicity is radiation esophagitis (21).…”
Section: Introductionmentioning
confidence: 99%
“…To date, DTX has been shown to be clinically useful as an active agent in CRT treatment regimens involving laryngeal/hypopharyngeal cancers (19). DTX has been used in combination with cisplatin as an agent for CRT in non-small cell lung cancer (20). A phase I/II study involving DTX and cisplatin with concurrent thoracic radiotherapy for locally advanced non-small cell lung cancer has shown that the dose limiting toxicity is radiation esophagitis (21).…”
Section: Introductionmentioning
confidence: 99%
“…N 2 skip lymphatic metastasis may be an earlier stage of lymphatic metastasis in NSCLC and its significance is similar to N l lymph node metastasis. In addition, some scholars proposed that dysregulation of gene expression associated with primary tumor is one of the most important factors influencing lymph node metastasis (20). Prenzel et al found that decreased expression of Bcl-2 and elevated expression of P21 were associated with N 2 skip metastasis in lung cancer (21).…”
Section: Discussionmentioning
confidence: 99%